Macbeth : Oxford school Shakespeare - Gill , Roma (New York : Oxford University press, 1977)
Macbeth is a tragedy by William Shakespeare about a brave Scottish general named Macbeth. After receiving a prophecy from three witches that he will become king, Macbeth, encouraged by his ambitious wife Lady Macbeth, murders King Duncan to take the throne. Once king, Macbeth becomes paranoid and commits more murders to stay in power, including his friend Banquo. Guilt and fear drive both Macbeth and Lady Macbeth into madness. Lady Macbeth dies, and Macbeth is eventually killed by Macduff, a nobleman. Malcolm, the rightful heir, becomes king, restoring order to Scotland.
Keywords: English novel; Oxford English novel